PENGARUH STRATEGI DIVERSIFIKASI TERHADAP RISIKO DAN KINERJA PERUSAHAAN REAL ESTATE DI INDONESIA - Edi Pranyoto (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2016)
Diversification is effort to develop business by extending number of segment in business andgeographical and also extends market share or develops various products. The purpose ofdiversification are to lesses risk and increases firm performance. Purpose of this research are toknow the influence of diversification on risk and firm performance. Type of data in this research ispanel data type, that suggested to use method of GLS ( Generalized Least Square). Where in thismethod can be analysed with two approach model, that is model affects fixed (FEM) and randommodel effects ( REM). From both the model can be determined the best model to be used in modelequation.The results showed that the diversification variable does not affectto total risk andunsystematic risk, but have effect to systematic risk of the company. Moreover, the results showedthat diversification significantly influence to the market performance of the company, but does notaffect to the company's operational performance. This matter happened because most real estatecompanies in Indonesia are diversified have the same effort with core business and have positivecorrelation with core business, so diversification does not have effect to firm performance. Result ofthis research indicates that diversification of business cannot less risk and cannot increase firmperformance.